The impact of intellectual capital on earnings management across the firm life cycle: A study of manufacturing companies listed on the IDX from 2020 to 2023 - Ruzami, Ashila Taqiyya; Tanzil, Nanny Dewi (Journal of Accounting Auditing and Business, 2025)
This study aims to determine how each element of intellectual capital affects earnings management based on the business life cycle. The data used for this study come from manufacturing companies listed on the IDX from 2020 to 2023. Overall, the research sample consists of 121 companies. The criteria for classifying a company's life cycle are based on the company's average sales growth. This study uses panel data regression analysis through the EViews 12 application. The results conclude that all intellectual capital components negatively influence earnings management, regardless of the company's life cycle. Meanwhile, HCE has a significant negative effect at the mature and decline stages but is insignificant during the growth stage. Additionally, SCE has a significant negative effect during the growth stage but an insignificant negative effect and an insignificant positive effect at the mature and decline stages. Furthermore, RCE shows a significant negative effect at the decline stage and an insignificant negative effect at the growth and mature stages. The last component, CEE, exhibits a significant negative effect at the mature stage but is insignificant during the growth and decline stages. Simultaneously, each intellectual capital component influences earnings management.